The stone cist conundrum: A multidisciplinary approach to investigate Late Neolithic/Early Bronze Age population demography on the island of Gotland. (August 2018) - Fraser, Magdalena; Sjödin, Per; Sanchez-Quinto, Federico; Evans, Jane; Svedjemo, Gustaf; Knutsson, Kjel; Götherström, Anders; Jakobsson, Mattias; Wallin, Paul; Storå, Jan
Abstract: The Late Neolithic period in Scandinavia [LN, c. 2350–1700 cal BCE] marks a time of considerable changes in settlement patterns, economy, and material culture. This shift also lays the foundation for the demographic developments in the Early Bronze Age [EBA, c. 1700–1100 cal BCE]. However, little is presently known regarding the developments from these time-periods on the island of Gotland in the Baltic Sea. During the Middle Neolithic period [MN, c. 3300–2350 cal BCE], Gotland was inhabited by groups associated with the Funnel Beaker culture [TRB, c. 4000–2700 cal BCE], and the sub-Neolithic Pitted Ware culture [PWC, c. 3300–2300 cal BCE]. Some indications of connections with the Battle Axe/Corded Ware cultures [BAC/CWC, c. 2800–2300 cal BCE] have also been found, but no typical BAC/CWC burials have been located on the island to date. Here, we investigate the chronological and internal relationship of twenty-three individuals buried in four LN/EBA stone cist burials; Häffinds, Hägur, Suderkvie, and Utalskog on Gotland. We present eleven mitochondrial genomes [from 23 X to 1271 X coverage], and twenty-three new radiocarbon dates, as well as stable isotope data for diet. We examine the local Sr-baseline range for Gotland, and present new Sr-data to discuss mobility patterns of the individuals. The genetic results are compared and discussed in light of earlier cultural periods from Gotland [TRB and PWC], and CWC from the European continent, as well as contemporaneous LN secondary burials in the MN Ansarve dolmen. We find that all burials were used into the EBA, but only two of the cists showed activity already during the LN. We also see some mobility to Gotland during the LN/EBA period based on Strontium and mitochondrial data. We see a shift in the dietary pattern compared to the preceding period on the island [TRB and PWC], and the two LN individuals from the Ansarve dolmen exhibited different dietary and mobility patterns compared to the individuals from the LN/EBA stone cist burials. We find that most of the cist burials were used by individuals local to the area of the burials, with the exception of the large LN/EBA Häffinds cist burial which showed higher levels of mobility. Our modeling of ancestral mitochondrial contribution from chronologically older individuals recovered in the cultural contexts of TRB, PWC and CWC show that the best model is a 55/45 mix of CWC and TRB individuals. A 3-way model with a slight influx from PWC [5%] also had a good fit. This is difficult to reconcile with the current archaeological evidence on the island. We suggest that the maternal CWC/TRB contribution we see in the local LN/EBA individuals derives from migrants after the Scandinavian MN period, which possible also admixed with smaller local groups connected with the PWC. Further genomic analyses of these groups on Gotland will help to clarify the demographic history during the MN to EBA time periods. Highlights: Multidisciplinary study of human remains from four LN/EBA stone cist burials on Gotland. Investigate population continuity from the MN TRB, PWC and CWC culture complexes through archaeogenetics Discuss regional Strontium isotope variation, chronology and mobility patterns within the burials The mitochondrial haplogroup composition is not consistent with population continuity from the MN period on the island. LN/EBA mobility is detected as well as, local individuals already established in the regions of the burials.